Free cash flow, debt-monitoring and managers' LIFO/FIFO policy choice - Gul, Ferdinand A (Journal of Corporate Finance, 2001)
This paper explores the explanatory power of Jensen's free cash flow hypothesis in managers' choice of LIFO versus FIFO. The association between FCF, and choice of inventory methods is based on the assumption that there is a potential conflict of interest between managers and shareholders when LIFO is the tax minimization method and that non-value-maximizing managers of firms with the FCF problem have incentives to choose FIFO, an income increasing method, in order to increase their compensation. However, since debt can act as a monitoring device and mitigate the agency problems of FCF, managers of firms with high FCF and high debt are less likely to choose FIFO than managers of firms with high FCF and low debt. The evidence is consistent with this expectation.